Mild respiratory illness in SARS-CoV-2 infection after vaccination in healthcare workers - Guanche Garcell, Humberto; Barban Arias, Reynaldo (International Journal of Infection Control, 2022)
COVID-19 after vaccination is a consequence of multiple factors, including the variable vaccine efficacy and the emergence of new viral variants. Sixteen cases of infection after completing the primary series of vaccination in healthcare workers (HCWs) are described. Ten cases had symptoms, mainly loss of smell (four cases), cough (four cases), fever (two cases), nasal discharge or obstruction (three cases), general malaise (two cases), and dyspnea and loss of taste in one case each. The median time between the second dose of the primary vaccination and the positive severe acute respiratory syndrome coronavirus 2 polymerase-chain reaction (PCR) was 132.5 days, and the median cycle threshold value at the time of diagnosis was 25.1. Laboratory tests performed at diagnosis showed results mostly in normal parameters, and in 10 cases, pulmonary findings suggestive of COVID-19 were described. The clinical course of the disease was satisfactory, without complications or sequelae at discharge. Conclusion: COVID-19 after vaccination in HCWs was mild, with a favorable course of the disease.